2014
DOI: 10.1371/journal.pone.0108992
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinal Nerve Fiber Layer Assessment of Spectral Domain Optical Coherence Tomography and Scanning Laser Polarimetry to Diagnose Preperimetric Glaucoma

Abstract: PurposeTo compare the abilities of peripapillary retinal nerve fiber layer (RNFL) parameters of spectral domain optical coherence tomograph (SDOCT) and scanning laser polarimeter (GDx enhanced corneal compensation; ECC) in detecting preperimetric glaucoma.MethodsIn a cross-sectional study, 35 preperimetric glaucoma eyes (32 subjects) and 94 control eyes (74 subjects) underwent digital optic disc photography and RNFL imaging with SDOCT and GDx ECC. Ability of RNFL parameters of SDOCT and GDx ECC to discriminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In the last two decades, retinal nerve fiber layer (RNFL) and optic nerve head (ONH) imaging devices for detecting glaucoma, such as optical coherence tomography (OCT), Heidelberg retinal tomography (HRT) and scanning laser polarimetry (GDx), were introduced in ophthalmic clinical practice to identify structural damages occurring early in glaucoma. However, the performance of these tests in clinical decision-making for detecting glaucoma is still debatable [ 6 ] and since their introduction, a large number of studies have been published on their diagnostic ability [ 7 9 ]. With such a large amount of evidence available, a high quality of reporting is crucial for clinicians to best appreciate the potential for bias and the internal/external validity of such studies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, retinal nerve fiber layer (RNFL) and optic nerve head (ONH) imaging devices for detecting glaucoma, such as optical coherence tomography (OCT), Heidelberg retinal tomography (HRT) and scanning laser polarimetry (GDx), were introduced in ophthalmic clinical practice to identify structural damages occurring early in glaucoma. However, the performance of these tests in clinical decision-making for detecting glaucoma is still debatable [ 6 ] and since their introduction, a large number of studies have been published on their diagnostic ability [ 7 9 ]. With such a large amount of evidence available, a high quality of reporting is crucial for clinicians to best appreciate the potential for bias and the internal/external validity of such studies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 24 Red free fundus photography is currently entitled as the gold standard for RNFL analysis. 25 Other objective devices available for RNFL evaluation were the scanning laser polarimetry and OCT. 26 29 Deleon-Ortega et al stated that similar diagnostic efficiency was found for all objective imaging techniques (HRT II, scanning laser polarimetry, and OCT), however no superiority was observed compared to the subjective assessment of the ONH stereophotography. 30 Andersson et al findings suggest that the sensitivity of MRA is superior to that of the average physician, but not including glaucoma experts.…”
Section: Discussionmentioning
confidence: 95%
“…Quite a few casecontrol studies have already reported good discriminating performances of SD-OCT and have thus validated its usefulness in glaucoma diagnosis. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Despite differences in study methodology design, SD-OCT machines evaluated, population sample selected or severity of glaucoma disease in each glaucoma group, all these studies have validated high diagnostic performances of OCT imaging technology with best values of AUC ranging from 0.786 to 0.978. Furthermore, the average peripapillary RNFL thickness was the most frequently described discriminating parameter followed by temporal parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous casecontrol studies have already shown good diagnostic performances of SD-OCT to detect glaucoma. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, only very few studies have been performed in a population setting. [30][31][32] In a systematic review of studies on imaging technology for diagnosing glaucoma, Michelessi et al 33 highlighted high risk of bias in these case-control studies, mainly related to patient selection as defined by the QUADAS 2 quality assessment tool, and raised concerns about the applicability of these results in iovs.arvojournals.org j ISSN: 1552-5783 clinical practice.…”
mentioning
confidence: 99%